Prof Dato’ Yaakob Bin Che Man, an excellent researcher and passionate mentor: glimpses from my memory - Mirghani, Mohamed Elwathig Saeed (2014)
I found him very friendly with an open mind regarding things related to Islam, academics and the general lifestyle. He was exploring new ideas and directed me and the group towards innovative thinking “thinking beyond the box“. Had an unquenchable thirst for new knowledge or information about knowledge. Intelligent, curious and passionate about investigating deeper to unearth more insight Always positive and was not afraid of failure. Excellent in writing and verbal communication so all can clearly understand the findings and what it means. He was able to see the bigger picture as well as the details to ensure that data is accurately presented and reported. He quickly developed a keenness on such normal observations because he saw in a way out of the common. We often found it easier to do one or the other, but Dato’ Prof. YCM always advised that we can do both simultaneously.